Expression of AmphiCoe, an amphioxus COE/EBF gene, in the developing central nervous system and epidermal sensory neurons. - Mazet, F; Masood, S; Luke, G; Holland, N; Shimeld, S (2004)
The COE/EBF gene family marks a subset of prospective neurons in the vertebrate central and peripheral nervous system, including neurons deriving from some ectodermal placodes. Since placodes are often considered unique to vertebrates, we have characterised an amphioxus COE/EBF gene with the aim of using it as a marker to examine the timing and location of peripheral neuron differentiation. A single COE/EBF family member, AmphiCoe, was isolated from the amphioxus Branchiostoma floridae. AmphiCoe lies basal to the vertebrate COE/EBF genes in molecular phylogenetic analysis, suggesting that the duplications that formed the vertebrate COE/EBF family were specific to the vertebrate lineage. AmphiCoe is expressed in the central nervous system and in a small number of scattered ectodermal cells on the flanks of neurulae stage embryos. These cells become at least largely recessed beneath the ectoderm. Scanning electron microscopy was used to examine embryos in which the ectoderm had been partially peeled away. This revealed that these cells have neuronal morphology, and we infer that they are the precursors of epidermal primary sensory neurons. These characters lead us to suggest that differentiation of some ectodermal cells into sensory neurons with a tendency to sink beneath the embryonic surface represents a primitive feature that has become incorporated into placodes during vertebrate evolution.